Effects of interval training on cardiovascular endurance and heart rate recovery in competitive male adolescent soccer players - Fahrial Amiq; Prayogi Dwina Angga; Adi Wijayanto; Andryas Yuniarto; Muhammad Yanuar Rizky (Universitas Nusantara PGRI Kediri, 2026)
Modern soccer requires players to sustain repeated high-intensity efforts, making VO₂Max and Heart Rate Recovery (HRR) important physiological indicators of performance. However, training practices in field settings often rely on intuition rather than objective physiological monitoring. This study aimed to examine changes in VO₂Max and HRR following a structured interval training program among adolescent soccer players. A pre-experimental one-group pretest–posttest design was employed as a preliminary intervention study. The sample consisted of 24 male players aged 16–17 years from Porma FC Malang, selected through purposive sampling based on fitness and competitive criteria. VO₂Max was measured using the Multistage Fitness Test (MFT). At the same time, HRR, defined as the decline in heart rate from peak exercise to one minute after exercise, was assessed using a pulse oximeter. Data were analyzed using descriptive statistics and paired sample t-tests with a significance level of p < 0.05. The results showed a statistically significant increase in VO₂Max from 43.23 to 50.02 ml/kg/min (p < 0.001, Cohen’s d = 3.45). HRR also showed a statistically significant change from 152.92 to 179.17 bpm (p < 0.001, Cohen’s d = 1.60). These findings suggest that structured interval training may be associated with changes in VO₂Max and post-exercise recovery responses among adolescent soccer players. Periodic MFT and HRR assessments may provide useful information for monitoring aerobic conditioning and recovery status during training programs. However, these findings should be interpreted cautiously due to the absence of a control group.